Identificación de Staphylococcus aureus meticilina resistente en muestras nasales del personal de salud del Hospital Básico 7BI Loja - Suing Quiñónez, Jenifer Lizette (2015)
Staphylococcus aureus is a Gram positive bacteria, it does not form spores and it does not have pilis nor flagella; it is a producer of coagulase so the difference in this genre. A very important aspect is the great facility of developing resistance to many antibiotics especially in hospitalized patients (Raul Cabello, 2007). According to the World Health Organization (WHO) it is estimated that people infected by Staphylococcus aureus resistant to methicillin (SARM) have a probability of dying by 64% higher than the infected for not resistant strains (Health, 2014). The colonization is frequently nasal where it acts as a reservoir being mainly affected the health personnel by MRSA, because they have direct contact with patients (Vicent Monje, 2011). For that reason, this study was proposed to identify Staphylococcus aureus in nasal samples of health personnel Basic Hospital Loja 7-BI; of these samples isolate the methicillin resistant strains and design an alternative proposal of improvement and prevention against MRSA. The study was carried out in 60 workers of Basic Hospital 7-BI Loja, where a nasal swab was performed, seeded in blood agar with incubation at 33 ° C for 24 h; then the identification was made with complementary tests as Gram, catalase, coagulase and salty mannitol with incubation at 33 ° C for 24h and; it proceeded to perform resistance testing by the diffusion method in disk with disks of cefoxcitina 30μɡ in agar Mueller Hinton and it incubated for 18 h at 33 ° C; besides it was used the positive control strain ATCC 43300 in all the procedure. Besides the positive control strain ATCC 43300 was used in all the procedure. 19 strains of S. aureus were isolated and 17 of them (89%) were methicillin sensitive and two of them (11%) were methicillin resistant. This study concluded in that there is the presence of S. aureus and there are strains resistant to the methicillin, which puts potential risk to patients of this health center, particularly the immunocompromised. Keywords: colonization, MRSA